Acidity and basicity interplay in amide and imide self-association - Vallejo Narváez, Wilmer E. (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Amides dimerise more strongly than imides despite their lower acidity. Such an unexpected result has been rationalised in terms of the Jorgensen Secondary Interactions Hypothesis (JSIH) that involves the spectator (C[double bond, length as m-dash]O(S)) and H-bonded (C[double bond, length as m-dash]O(HB)) carbonyl groups in imides. Notwithstanding the considerable body of experimental and theoretical evidence supporting the JSIH, there are some computational studies which suggest that there might be other relevant intermolecular interactions than those considered in this model. We conjectured that the spectator carbonyl moieties could disrupt the resonance-assisted hydrogen bonds in imide dimers, but our results showed that this was not the case. Intrigued by this phenomenon, we studied the self-association of a set of amides and imides via(1)H-NMR, (1)H-DOSY experiments, DFT calculations, QTAIM topological analyses of the electron density and IQA partitions of the electronic energy. These analyses revealed that there are indeed repulsions of the type O(S)···O(HB) in accordance with the JSIH but our data also indicate that the C[double bond, length as m-dash]O(S) group has an overall attraction with the interacting molecule. Instead, we found correlations between self-association strength and simple Brønsted–Lowry acid/base properties, namely, N–H acidities and C[double bond, length as m-dash]O basicities. The results in CDCl(3) and CCl(4) indicate that imides dimerise less strongly than structurally related amides because of the lower basicity of their carbonyl fragments, a frequently overlooked aspect in the study of H-bonding. Overall, the model proposed herein could provide important insights in diverse areas of supramolecular chemistry such as the study of multiple hydrogen-bonded adducts which involve amide or imide functional groups.